Geenetic relationship among the negrito (Semang) tribes of peninsular Malaysia: the microsatellite approach - Peng, Hoh Boon (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
One of the approaches to identify susceptibility genes for complex disorders is to focus on genetically isolated populations such as the Orang Asli populations rather than the general population, because the environmental variation may be lower and the genetic make-up of these populations is expected to be less complex. Various markers have been used for genetic linkage mapping. Microsatellite markers are of interest to many researchers as they are more polymorphic and hence more informative (typically having more than ten alleles). Hence, they offer greater statistical power for the data analysis, whether by parametric analysis of large families, or nonparametric analysis of sib-pairs etc. The Negritos (Semang}, believed as the first Orang Asli group to arrive in Peninsular Malaysia more than 10,000 years ago. They are divided into six subgroups, namely, Kensiu, Bateq, Mendriq, Jahai, Lanoh and Kintak. Therefore, studying this ethnic group could be useful for fine scale mapping as well as better understanding for the evolutionary and biological process leading to certain disease. The objective of the study is to generate the genotype data of 10 selected microsatellite markers among the 3 Negrito tribes in Kelantan state, and later to compare the allele frequencies with other ethnic groups from publicly available data. 10 markers with the highest heterozygosities were chosen (Appendix I) and seven were applied. The observed heterozygosities of the seven loci were found to be significantly lower than those found in the published database, except for DlS243, suggesting the possibility of inbreeding and genetic drift in the Negrito population. A larger scale investigation using more samples and markers should be done to confirm the results. Such study would also help in our understanding of pre-historic human migration in the Malay Archipelago which until today remains largely a mystery besides providing information for forensic profiling and the identification of complex diseases which may be prevalent in certain populations. Comprehensive Technical Report Official consent was obtained from the JHEOA and the discrict representative respectively. Samples were collected from Pos Lebir, Kuala Lar, Sg Rual and Aring. A total of 105 samples were collected. However, only 62 were included into the study after a stringent sample inclusion criteria. This includes 18 Bateqs, 14 Mendriqs and 30 Jahais. The numbers of individuals in the tribes are decreasing and majority of them practice consanguineous marriage, or inter-tribe marriage. Currently, there are about 1000 individuals in the Jahai tribe; 700 in Bateq tribe; and less than 80 individuals in Mendriq tribe. Thus, it is of reasonable that the sample collection is rather lesser than that of expected. I 0 markers with the highest heterozygosities were chosen (Appendix I). Optimizations were done and 7 of the primers were successful. These markers were amplified on the samples and the fluorescent-labeled fragments were electrophoresed through ABB I 00 and analyzed using GeneScan analysis software. The allele frequencies of the loci were calculated. Heterozygosities of the markers and possible error in genotyping or allele calling were checked and tested with Hardy-Weinberg's Equilibrium. Due to time '· constraint, the remaining SIR primers were not further optimized. The observed heterozygosities of the seven loci were found to be significantly lower than those found in the published database, except for DI 8243. The lower observed heterozygosity among the Negritos compared to other published data suggested the possibility of inbreeding and genetic drift in the Negrito population in general. Analysis with a low value of Fst (0.0694) indicating the high genetic similarity among the three tribes, supported the suggestion; while the number of individuals in the tribes further proven the findings in this study. If carried out using sufficient sample sizes and loci, a study such as this would be helpful in understanding pre-historic human migrations in the Malay Archipelago which currently remains largely unknown. On top of that, it may contribute additional information to forensic profiling and the identification of complex diseases which may be prevalent in certain populations.